Quartz textural and trace-element geochemical constraints on the origin of lode gold deposits: a case study of the Yanzhupo deposit in Jiangnan Orogen (South China) - Peng, Nengli; Shen, Hongjie; Liao, Jia (Frontiers in Earth Science, 2025)
The Jiangnan Orogen (South China) is endowed with many important gold deposits, whose genesis remains controversial. The Yanzhupo is a representative gold deposit (2.50 t Au @ 2.52 g/t) in the Jiangnan Orogen, characterized by multi-stage quartz formation. Its mineralization can be divided into three stages (I) quartz-ankerite-pyrite (II) quartz-ankerite-chlorite-pyrite-gold, and (III) quartz-ankerite-calcite-pyrite. Multiple generations of quartz were identified at Yanzhupo. Stage I quartz (Qz1) commonly coexists with pyrite and is coarse-grained, and texturally homogeneous. Stage II quartz (Qz2) is divided into two generations, namely, Qz2a and Qz2b, and the homogeneous Qz2a is often replaced by the veined/stockwork Qz2b. Stage III quartz (Qz3) comprises two generations of quartz, namely, the earlier, texturally homogeneous Qz3a, and the younger Qz3b that replaced Qz3a. Qz1 is Ti-rich (median: 0.743 ppm) and Al-depleted (median: 294 ppm), indicating that it was formed at high temperatures and pH levels. The ensuing drop in temperature and pH favored the formation of Qz2a. However, the abrupt decrease in Al concentration from Qz2a (median: 1,383 ppm) to Qz2b (median: 120 ppm) suggests that it was created at a high pH, which might have been caused by an intense water-rock interaction, resulting in Stage II Au precipitation. Finally, the sealing of fractures by veins may have resulted in the production of Qz3 in stable settings, evidenced by the As-rich and Ti-depleted Qz3 than Qz2b. The Yanzhupo Au deposit has Al and Ti contents and Al/Ti ratios that are similar to those found in magmatic-hydrothermal deposits, implying that it is likely of magmatic-hydrothermal origin. These findings show that the coupled examination of quartz texture and geochemistry can provide important clues to the mineralization history, origin of gold deposits, and the distribution characteristics of gold mineralization, and give vital insights into the origin of Au mineralization in the Jiangnan Orogen (South China).